Preference of instrumental values versus the sens of sicurity among the singles and people living in costant marriage relationships - Głaz, Stanisław (Studia Psychologica: Theoria et praxis, 2009)
There is a group of people in our society, who have chosen a certain life style. They want to tell us they do not live in a constant relationship. We call them singles. The author is interested in two issues. These are instrumental values i.e. the most general ways of behaviour of a human being living in a certain society and the sense of security. It is believed that the singles prefer another system of instrumental values and are characterised by a different structure of the sense of security than the people living in a constant married relationship. It is also assumed that different instrumental values influence significantly the sense of security of the singles and different values influence the sense of security of the people living in constant married relationship. The author, interested in these issues, decided to answer the following ąuestions: 1. Do the gender and the lifestyle differentiate the preferred by the examined individuals instrumental values, and if yes, which ones? 2. Do the gender and the lifestyle differentiate the sense of security, and if yes, to what extent? 3. To what degree and by which instrumental values the variance of the sense of security in the group of singles and in the group of people living in constant married relationship are explained? The research took place in Nowa Huta district of Krakow in 2006. People who are not in a permanent relationship - singles and people living in constant married relationship were examined. The sample of 100 individuals aged 32-36 was taken into account. Rokeach Value Survey Questionnaire was used to determine instrumental values preferences both for the singles and the people living in constant married relationship. Uchnast Sense of Security Questionnaire was used to determine their sense of security. Tenderness and treating the other with consideration appeal more to the singles. They are self-reliant, more self-sufficient and more effective in their activities than married people. Whereas people living in constant married relationship are polite, pay more attention for keeping order and are more conscientious than the singles. Both the singles and people living in constant married relationship are characterised by lack of self- confidence, lack of sense of stability and lack of sense of having things sorted out. Strong sense of intimacy is found in both groups, though it shows more clearly within the group of the singles. The sense of security of people living in a constant married relationship is substantially influenced by such instrumental values as effectiveness, politeness and loyalty. The sense of security of the singles is more influenced by ambition, self-reliance, tolerance, understanding and loyalty.